Exploring and Analyzing ESG Activity Evaluation Factors of Sports Brands using Delphi and AHP Techniques - Min-Ah Ryu (Cheyuk gwahag yeon-gu, 2023)
PURPOSE This study aimed to identify and establish ESG activity assessment factors tailored for sports brands, offering a foundational framework for fostering sustainability within the sports industry. METHODS A Delphi survey was conducted between December 1, 2022, and January 31, 2023, involving university professors, sports brand executives, ESG researchers, sports marketing majors , a nd sports brand influencers. Data were analyzed using SPSS WIN 24.0 and MS Excel, encompassing research subject classification, consistency verification, and empirical analysis. RESULTS The assessment of ESG activity evaluation factors of sports brands revealed that governance, social, and environmental dimensions ranked in descending order of relative importance. Among specific evaluation criteria, the adoption of employee ethics regulations was deemed paramount in the governance evaluation area, while support for stakeholder welfare and social well-being took precedence in the social evaluation category. In the environmental sector, the production and delivery of eco-friendly, durable products held the highest significance. Further analysis, considering the weighted priorities of all evaluation factors, emphasized the importance of factors, such as the adoption of employee ethics regulations, support for stakeholder welfare, social well-being, and the production and delivery of eco-friendly, durable products. Conversely, disclosure of company information and issues, support for the underprivileged, and general shareholders' meeting or agenda for the protection of shareholders' rights and interests ranked lower. CONCLUSIONS In summary, this study validates the role of governance (G) aspects within ESG activities for sports brands, alongside environmental and social dimensions. It highlights the importance of a balanced ESG framework, particularly in an era marked by heightened social responsibility awareness among consumers. Prioritizing governance in marketing strategies not only distinguishes sports brands but also necessitates impactful promotion and advertising efforts.